Artistes afro-brésiliennes, d’un siècle à l’autre - Giunta, Andrea (AWARE : Archives of Women Artists, Research and Exhibitions, 2021)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Holding Space: A Roundtable Conversation on Trauma and Teaching in the Museum - DeLos Santos, Jenevieve; Lee, Kathleen Pierce with Key Jo; Martínez, Gabriela; Reaves, Damon; Scruggs, Dalila (Art Journal Open, 2021)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Musee Migrant – MuMi - Clériga Morales, Deyanira; Valenzuela Arámburo, Pável; Ledón Pereyra, Aldo Jorge (revue Periferias, 2019)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Imaginarios y estrategias decoloniales - Ferrera-Balanquet, Raúl Moarquech (Estudios Artísticos, 2018)
Enunciando el delinking de la matriz moderna/ colonial, este artículo imagina un territorio crítico teórico creativo partiendo de la aesthesis decolonial con el fin de dialogar con una serie de hacedores culturales que emplean estrategias creativas decoloniales en proyectos creativos. Un acercamiento a la exposición Haceres Decoloniales (2015) realizada en Bogotá, ofrece la oportunidad de conversar sobre el hacer creativo de Benvenuto Chavajay, Rosa Tisoy Tandoy y Marco Alonso Roa. Los efectos de la colonialidad sonora conllevan a dialogar con la artista maya k´iche Sandra Monterroso y el creador maya yucateco Isaac Carrillo Can. Discursamos sobre el proyecto Espejo Negro (2010) de Pedro Lasch y el mural Las Aguas Sagradas de La Llorona (2004) de la artista xicana Juana Alicia. Terminamos con una interpretación crítica sobre el proyecto Mariposa Memoria Ancestral (2013-2015), y el performance multidisciplinario Whip It Good (2013) de la artista danesa trinitobaguense Jeannette Ehlers. En reliant la déconnexion de la matrice moderne / coloniale, cet article imagine un territoire créatif- théorique-critique à partir de l’aesthésis décoloniale, afin de dialoguer avec une série d’acteurs culturels qui utilisent des stratégies décoloniales créatives dans des projets créatifs. Une approche de l’exposition Haceres Decoloniales (2015) tenue à Bogotá, offre l’occasion de parler du travail créatif de Benvenuto Chavajay, Rosa Tisoy Tandoy et Marco Alonso Roa. Les effets de la colonialité sonore impliquent un dialogue avec l’artiste maya k’iche Sandra Monterroso et le créateur maya yucatècque Isaac Carrillo Can. Nous parlons du projet Espejo Negro (2010) de Pedro Lasch et de la peinture murale Las Aguas Sagradas de La Llorona (2004) de l’artiste chicane Juana Alicia. Nous terminons avec une interprétation critique du projet Mariposa Memoria Ancestral (2013-2015) et la performance pluridisciplinaire Whip It Good (2013) de l’artiste danois né en Trinité-et-Tobago Jeannette Ehlers.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Collecting African American Art: the Museum of Fine Arts, Houston - Franklin, John Hope; Wardlaw, Alvia J (Museum of Fine Arts ; Yale University Press, 2009)
This important book showcases institutional and private efforts to collect, document, and preserve African American art in American's fourth largest city, Houston, Texas. Eminent historian John Hope Franklin's essay reveals his passionate commitment to collect African American art, while curator Alvia J. Wardlaw discusses works by Robert S. Duncanson, Henry Ossawa Tanner, Horace Pippen, and Bill Traylor as well as pieces by contemporary artists Kojo Griffin and Mequitta Ahuja. Quilts, pottery, and a desk made by an African American slave for his daughter contribute to the overview. The book also focuses on the collections of the "black intelligentsia," African Americans who taught at black colleges like Fisk University, where Aaron Douglas founded the art department. A number of the artists represented were collected privately before they were able to exhibit in mainstream museums.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #3 The vanishing Curator - Game Studies India Adda (Game Studies India Adda, 2020)
Playing back to the Empire, in videogames, is rife with tensions. The imperialist sentiment inherent in reverse-colonist discourse featured in most strategy-based videogames like Europa Universalis IV, where the player could conquer Europe playing for the Marathas, has been noted by Souvik Mukherjee (2017) as playing into the colonial logic while futilely trying to challenge it. Studio Oleomingus, an Indian two-man game studio, is one of the few involved in a different experiment. Their mythical game Somewhere, chronicling a postmodernist search for identity and narrative in the forgotten city of Kayamgadh, has generated significant spin-offs into its universe. With attention to one such spin-off, I will focus critical attention on the issue of the postcolonial gaming of the Museum in A Museum of Dubious Splendors. I will examine the New Museological implications of A Museum of Dubious Splendors, keeping in mind Museologist Eilean Hooper-Greenhill’s assertion of museums embodying “the power to name, to represent common sense, to create official versions, to represent the social world, to represent the past” (Hooper-Greenhill 2001: 2). Oleomingus’ own description of A Museum, as an adaptation of edited, mangled, contested short stories by a fictional Urdu writer, Mir Umar Hassan, eschews the linear narrative production of the colonial museum for a game of meanings, where the player enters rooms according to his choice and constructs his/her own “quiet game about prosaic objects and spurious histories.” ("A Museum" 2018) The paper would take this into account and examine the reconceptualization of the museum space with respect to James Clifford’s sense of museums being “contact zones”: A Museum’s lack of any curator, with its curious blend of colonial and native tales and banal objects defamiliarised by “spurious histories” lends itself to questions of playing the Empire back according to a different episteme, through subaltern histories that the colonial museum space silenced. Paying close attention to the question of postcolonial spatiality in this game, I will analyze the historiographical implications of these identity-scatterings and recuperations at constant play in the structure of the game. Keywords: Museum Studies, Thing Theory, Game studies, Marginal identity, Postcolonial Studies
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Decolonial AestheSis at the 11th Havana Biennial - Ferrera Balanquet, Raul Moarquech; Rojas-Sotelo, Miguel (Social Text Online, 2013)
The written curatorial statement from the organizing committee of the 11th Havana Biennial arrived via email the same day that we were preparing a dossier for the Romanian magazine IDEA. As we put together a brief history of “Decolonial Aesthetics” meetings and some portions of the “Decolonial Manifesto,” we discussed the need to bring to the biennial some of the critical and creative processes emanating from the decolonial collective. Previous editions of the biennial were overcharged with doses of “postmodernity,” marginal notes on the “postcolonial” condition, and celebrations of the “altermodern” (with its postproduction and relational dimensions). These were present in the curatorial practices, as well as in several of the presentations at the Theoretical Forum during the 2006 and 2009 editions. As we kept reading through the Biennial‘s curatorial statement, its content promoted a heated discussion among us where the idea of presenting a panel on decolonial aestheSis at the Havana Biennial became seen as not only relevant, but also, and above all, necessary.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 5-Auteur.rice PANDC; _Nettoyé